Validation of Planning Target Volume Margins by Analyzing Intrafractional Localization Errors for 14 Prostate Cancer Patients Based on Three-Dimensional Cross-Correlation between the Prostate Images of Planning CT and Intrafraction Cone-Beam CT during Volumetric Modulated Arc Therapy - Kenshiro Shiraishi (BioMed Research International, 2014)
Time-averaged intreatment prostate localization errors were calculated, for the first time, by three-dimensional prostate image cross-correlation between planning CT and intrafraction kilovoltage cone-beam CT (CBCT) during volumetric modulated arc therapy (VMAT). The intrafraction CBCT volume was reconstructed by an inhouse software after acquiring cine-mode projection images during VMAT delivery. Subsequently, the margin between a clinical target volume and a planning target volume (PTV) was obtained by applying the van Herk and variant formulas using the calculated localization errors. The resulting PTV margins were approximately 2 mm in lateral direction and 4 mm in craniocaudal and anteroposterior directions, which are consistent with the margin prescription employed in our facility.